2018
DOI: 10.1021/acsaem.8b01049
|View full text |Cite
|
Sign up to set email alerts
|

Noble-Metal-Free MoS2 Platelets with Promising Catalytic Performance in Hydrogen Evolution Reaction for the Post-Lithium-Ion Battery

Abstract: In search of a practical alternative catalyst to costly and rare noble metals for hydrogen evolution reaction (HER), here we propose a lamellar electrode architecture out of engineered 2D MoS 2 platelets that are stable in harsh electrochemical conditions, densified in the catalytically active sites, and enhanced in the interlamellar charge transfer. Energetic ion bombardment such as Ar ion beam milling (IBM) as a large-scale surface engineering technique can successfully create numerous edge states onto the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The HER activity of pristine ZnO has been reported in our previous article. The results also infer that the charge can be easily transferred in WZO nano-heterostructures as compared to pristine WS 2 . , ,, …”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The HER activity of pristine ZnO has been reported in our previous article. The results also infer that the charge can be easily transferred in WZO nano-heterostructures as compared to pristine WS 2 . , ,, …”
Section: Resultsmentioning
confidence: 76%
“…The theoretical analysis also revealed that alloying or heterojunction formation in TMDCs can generate strain in the lattice to trigger inert chalcogen edges and create strained chalcogen vacancies. , Wang and co-workers demonstrated that TM doping with MoS 2 clearly activates the inert S-edges as equal as that of Mo-edges . It can be also noted from the literature that the improved HER because of alloying and heterojunction formation is due to the fact that the Gibs energy change ΔG H shifts toward zero because of the generation of strain at chalcogen edges and Δ G H ≈ 0 is fulfilled for absorption of hydrogen. , Moreover, the concentration of active sites greatly depends on important parameters, such as surface-to-volume ratio, crystallinity, defect concentration, electrical conductivity, porosity, and so forth. These parameters strongly depend on the morphology of the nanomaterial-based catalysts. , Table shows the performance of the present catalyst is either comparable or even better than the previous reports on TMDC-based catalysts.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Two-dimensional transition metal dichalcogenides (2D-TMDCs) have shown great promise for technical applications in a variety of fields, including optoelectronics, electronics, , photocatalysis, electrochemical catalysis, etc. owing to their optimized physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) semiconductor-based few-to-monolayer transition-metal dichalcogenides (TMDCs) and their hybrids with other 2D/one-dimensional/three-dimensional nanomaterials as heterostructures have recently attracted challenging applications due to their unique structures and superior properties that none of the individual conventional 2D nanomaterials could have. , Among the large family of 2D semiconductor TMDCs, Molybdenum disulfide (MoS 2 ) is a prominent 2D layered material, composed of Mo atoms sandwiched between two layers of hexagonally close-packed sulfur atoms. Because of the peculiar layered structure and the thickness-dependent indirect to direct band gap nature, MoS 2 has come up for use in a variety of applications, particularly lithium battery, solid lubricant, sensors, hydrogen production, and photocatalytic applications. , The graphenelike structure and direct band gap at the few-to-monolayer structure captures visible-to-near-IR photon energies, which helps for use in many optoelectronic applications. , However, in its pristine form as single semiconductor, MoS 2 has drawbacks for use in commercial practical applications in the above-mentioned fields because of the intrinsic defects . To overcome this, it is desirable to design composites and heterostructures and limit the inherent defects.…”
Section: Introductionmentioning
confidence: 99%